Electrical Cochlear Response as an Objective Measure of Hearing Threshold and Hearing Performance Evaluation in Pediatric Cochlear Implant Users - Quintana López, Agar Karina; Beltran Vargas, Nohra Elsy; Granados Trejo, Maria del Pilar; Cornejo-Cruz, Juan Manuel (Revista Mexicana de Ingenieria Biomedica, 2020)
The difficulties of applying the audiometry in pediatric populations and its methodological limitations in implanted patients have spurred the development of new alternative auditory evaluation methods. This study aimed to show an objective method to estimate hearing thresholds in pediatric cochlear implanted patients through Electrical Cochlear Response (ECR) and to quantify the hearing performance by using an Auditory Skills Questionnaire (ASQ) and a Calibrated Sounds Test (CST) designed on purpose. Eighteen implanted patients, 1-6 years old underwent standard audiometry, ECR, and ASQ in two evaluation sessions T1 and T2. At T2, in addition, patients underwent CST. For patients ≤3 years old (G1), Pure Tone Averages PTA and PTAECR showed a statistically significant difference between them at T1 and T2. At T2 improvements in audiometric and ECR thresholds were observed (p<0.05), regarding T1. Patients older than 3 years (G2) had significantly better ASQ and CST scores. CST detection scores at 40 dBHL for groups G1 and G2, 36% and 70% respectively, showed a better relationship to ECR thresholds. The relationship observed between ECR thresholds and CST detection scores seems to confirm that ECR brings the feasibility of objective hearing threshold estimation and provides a better frequency resolution than audiometry.